2018
DOI: 10.1051/matecconf/201822801009
|View full text |Cite
|
Sign up to set email alerts
|

A Study on a Predictive Model of Customer Defection in a Hotel Reservation Website

Abstract: This paper examines a hotel reservation website's customer defection. Applying statistic and data mining technology including logistic regression and random forests, we examine customer database to identify the attributes that affect customer attrition and develop a model of customer defection in the hotel reservation website. The empirical evaluation results showed the model has 78.9% accuracy, which suggest that the proposed churn prediction technique exhibits satisfactory predictive effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The results showed that the random forest algorithm can better solve the classification problem of CCP, and the accuracy of the prediction model reached 94%. In the research of Han [10], the customer churn of hotel reservation websites has been investigated in China. In this research, logistic regression and random forest algorithms were used to identify the characteristics that affect customer churn.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the random forest algorithm can better solve the classification problem of CCP, and the accuracy of the prediction model reached 94%. In the research of Han [10], the customer churn of hotel reservation websites has been investigated in China. In this research, logistic regression and random forest algorithms were used to identify the characteristics that affect customer churn.…”
Section: Literature Reviewmentioning
confidence: 99%